Integrating Pesantren Values into Islamic Religious Education for Character Strengthening - Ahmad Wifaqi Shiddiqi; Asriana Kibtiyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines pesantren-based Islamic Religious Education learning strategies in strengthening students’ character at MTs Madrasatul Qur’an Tebuireng Jombang. The study aims to analyze the implementation of pesantren-based learning, identify supporting and inhibiting factors, and examine its contribution to students’ moral and spiritual development. This research employed a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and documentation involving school principals, Islamic Religious Education teachers, pesantren supervisors, and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that character strengthening is implemented through the integration of religious learning, worship habituation, Qur’anic recitation, congregational prayers, moral discipline, and teacher exemplification within students’ daily activities. The pesantren environment functions as a moral ecosystem that continuously reinforces Islamic values through collective educational culture. Supporting factors include strong religious traditions, teacher commitment, parental support, and structured pesantren regulations, while inhibiting factors involve students’ adaptation difficulties, diverse family backgrounds, and the influence of digital culture. The study concludes that pesantren-based learning strategies effectively strengthen students’ discipline, responsibility, honesty, independence, and spiritual awareness. This research contributes theoretically to Islamic education discourse by emphasizing the importance of integrating religious values, educational culture, and moral habituation within contemporary character education.